2006
DOI: 10.1112/s0024609306018194
|View full text |Cite
|
Sign up to set email alerts
|

Feynman–kac Formulas for Black–scholes-Type Operators

Abstract: Abstract. There are many references showing that a classical solution to the Black-Scholes equation is a stochastic solution. However, it is the converse of this theorem which is most relevant in applications and the converse is also more mathematically interesting. In the present article we establish such a converse. We find a Feynman-Kac type theorem showing that the stochastic representation yields a classical solution to the corresponding Black-Scholes equation with appropriate boundary conditions under ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…The proof of Proposition 5.2 resembles the arguments in [30]. For similar results, see Section 3.5 in [39], Theorem 5.6.1 in [3,21,27,48].…”
Section: Connections With Parabolic Partial Differential Equationsmentioning
confidence: 72%
“…The proof of Proposition 5.2 resembles the arguments in [30]. For similar results, see Section 3.5 in [39], Theorem 5.6.1 in [3,21,27,48].…”
Section: Connections With Parabolic Partial Differential Equationsmentioning
confidence: 72%
“…The relationship between CEV stochastic equations and PDEs was established by Janson and Tysk [23] who proved a Feynman-Kac type theorem: precisely, they showed that, if the payoff function ϕ is continuous and polynomially bounded (i.e. |ϕ(S)| ≤ C(1 + S m ) for some C and m), then the function C in (4.39) is the unique, polynomially bounded classical solution…”
Section: Numerical Testsmentioning
confidence: 99%
“…For a more recent discussion of the well-posedness of the problem, see also [20]. In the numerical experiments here, we will use (6.4) as in [10] even if it is not needed.…”
Section: Multi-asset American Option Pricingmentioning
confidence: 99%